PENENTUAN KLASIFIKASI TINGKAT KESEJAHTERAAN KELUARGA MENGGUNAKAN METODE NAIVE BAYES PADA KECAMATAN PASAR JAMBI - Purnamasari, Ade; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2019)
Large and quality population is one of the basic capital and dominant factors for national develtopment.The large number of population data in the Pasar Jambi Distric has not produced a useful knowledge forthe sub-district. This study will classify the level of family welfare using population data in Pasar JambiDistrict by utilizing data mining science classification techniques. The classification in this study islimited to prototype. The method that will be used is the Naive Bayes method. Naive Bayes is a method inthe field of probability and statistic for classifying a class. The resulting classification is Pre-prosperous,Prosperous 1 and Prosperous 2. The results of classification prediction based on training data found 180families classified as Pre-prosperous, 2.454 families classified as Prosperous 1, and 773 familiesclassified as Prosperous 2. The result of accuracy obtained are said to be close to 1, 0,98 with an errorvalue of 0,02. This classification technique can facilitate family planning field officers (PLKB) indetermining the level of family welfare.